The conditions of chondrule formation, Part II: Open system. (15th January 2016) - Friend, Pia; Hezel, Dominik C.; Mucerschi, Daniel
Abstract: We studied the texture of 256 chondrules in thin sections of 16 different carbonaceous (CV, CR, CO, CM, CH) and Rumuruti chondrites. In a conservative count ∼75% of all chondrules are mineralogically zoned, i.e. these chondrules have an olivine core, surrounded by a low-Ca pyroxene rim. A realistic estimate pushes the fraction of zoned chondrules to >90% of all chondrules. Mineralogically zoned chondrules are the dominant and typical chondrule type in carbonaceous and Rumuruti chondrites. The formation of the mineralogical zonation represents a fundamentally important process of chondrule formation. The classic typification of chondrules into PO, POP and PP might in fact represent different sections through mineralogically zoned chondrules. On average, the low-Ca pyroxene rims occupy 30 vol.% of the entire chondrule. The low-Ca pyroxene most probably formed by reaction of an olivine rich chondrule with SiO from the surrounding gas. This reaction adds 3–15 wt.% of material, mainly SiO2, to the chondrule. Chondrules were open systems and interacted substantially with the surrounding gas. This is in agreement with many previous studies on chondrule formation. This open system behaviour and the exchange of material with the surrounding gas can explain bulk chondrule compositional variations in a single meteorite and supports the findings from complementarity that chondrules and matrix formed from the same chemical reservoir.